If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -6(0) = 48 Multiply -6 * 0 8x + 0 = 48 Anything times zero is zero. 8x + 0 = 48 Reorder the terms: 0 + 8x = 48 Remove the zero: 8x = 48 Solving 8x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '8'. x = 6 Simplifying x = 6
| 3lnx^2-lnx=0 | | 4x-3(2-3x)=20 | | 16t=156 | | 6x+3y=195 | | 8x-2(4x-5)=20 | | 3t^2+23t-8=0 | | 8x-5(0)=120 | | l=500/x | | 2lnx-ln(2x-1)= | | .4x+x^2=.96 | | 8x-8x-5=20 | | 5m=3msquared | | 4x-2=5x+11 | | r^3+24r-160=0 | | .2x+x^2=.99 | | 3t^2+23t-8=o | | 8+10x=26+x | | 0.06x=1730 | | 2X+3X+4=what | | .04+.4x+x^2=1 | | 2(3x+8)=5(x-7) | | q=8p-45 | | 42y+5=71 | | 11x-17=8x+9 | | 12x+3-6x-3=90 | | 9q+54=3q+90 | | 8+2b=10 | | 4j-4=2j+20 | | 3[5-4(4-c)]-5=5[3(5c-4)+2]-26 | | -6+y^2=10 | | x^2+.4x=.96 | | -2x^2+8x-56=0 |